2018
DOI: 10.1093/jas/sky198
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the excretion of urinary metabolites in goats and sheep to evaluate spot sampling applied to protein nutrition trials

Abstract: The main objective of this study was to establish a protocol to validate urine spot samples to estimate N excretion and microbial synthesis in goat and sheep; and to study factors that affect daily creatinine and purine derivatives (PD) urinary excretion. Also a performance trial was carried out to compare goat and sheep slaughtered after different feedlot periods. Twelve Boer goats (20.6 kg ± 3.4 initial BW) and 12 Dorper sheep (18.4 kg ± 2.3 initial BW), all 4-mo-old, males, were used. Eight animals (4 goats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The quadratic increase in PD excretion with increasing SC+UAS inclusion (Table 6) could be a consequence of the same effect, as observed for DM intake, given the correlation between them when DM intake is adjusted for BW [16,71]. For example, greater PD excretion was observed at 345 g SC+UAS/kg DM, which matched the greater DM intake (g/kg BW) at 343 g SC+UAS/kg DM.…”
Section: Urinary Volume Pd and Mpsmentioning
confidence: 54%
“…The quadratic increase in PD excretion with increasing SC+UAS inclusion (Table 6) could be a consequence of the same effect, as observed for DM intake, given the correlation between them when DM intake is adjusted for BW [16,71]. For example, greater PD excretion was observed at 345 g SC+UAS/kg DM, which matched the greater DM intake (g/kg BW) at 343 g SC+UAS/kg DM.…”
Section: Urinary Volume Pd and Mpsmentioning
confidence: 54%
“…As there was no difference in the circadian rhythm of the PDE and PDC index, these were tested in the spot urine sample obtained at 4 h after the morning feeding, as suggested by [25,33,34]. Muszczyñski et al [25] did not find a modifying effect of food (feeding time) on diurnal renal activity and reported a lack of GFR rhythms in goats with permanent food access.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative to 24-h total urine collections is the possibility of using the concentration ratio of purine derivatives (PD) to creatinine (PDC index) in spot urine samples and the daily creatinine excretion as estimators of the PD excretion [27,[30][31][32]. The spot urine collection technique to obtain the urinary excretion of PD is based on the principle that daily creatinine excretion does not vary with diet and only a sample of urine collected at 4 h after morning feeding is suitable [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the urea/creatinine ratio of the finishing period was higher at 4:00 p.m. than before, which would reflect a higher urea synthesis than creatinine in the last sampling, possibly linked to postprandial digestion. Other works have observed that blood creatinine concentration usually had few diurnal fluctuations (6:00 a.m. to 6:00 p.m.), but it was higher during diurnal than nocturnal sampling periods [ 41 ].…”
Section: Discussionmentioning
confidence: 99%